Willingness to Adopt Opt-Out Organ Donation System: Saving Life from Death - Abbas, Sana; Naeem, Saquib; Rafique, Aisha; ., Sajjad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To study the information, supposition and impression of the general population concerning organ donation and transplantation in Pakistan.Study Design: Cross-sectional analytical survey.Place and Duration of Study: Study was conducted at Tertiary Care Hospital, from Jan to Aug 2020.Methodology: We used the web-based questionnaire, devised from relevant studies and National Health Service (NHS) protocols. The questionnaire comprised of 20 multiple-choice questions (MCQs) in addition to demographic profile,distributed among the general population (n=1000) which assessed basic knowledge regarding organ transplantation and willingness for donation.Results: One thousand participants were enrolled in the study. The age range was 24–61, with a mean age of 36.66±9.00 years.933(93.3%) participants believed organ donation should be mandatory, and 600(60%) expressed willingness to donate or accept organ donation. In addition, 933(93.3%) participants believed in arranging awareness campaigns, and 1000(100%) had an opinion of establishing a convenient donor registration system.Conclusion: There are momentous awareness and willingness for organ donation; therefore, befitting tactics can enhance organ donation in Pakistan, and this issue will no longer be considered a haunted one.